Equilibrium orbits U-240 cyclotron calculation - O. E. Valkov; O. K. Zaichenko (Âderna Fìzika ta Energetika, 2013)
Methods of the U-240 cyclotron equilibrium orbits calculation and correction of the isochronous field, calcu-lated by the analytical formulas are described.